Exploration with a computer : geoscience data analysis applications - Green, William R. (Computer methods in the geosciences, 1991)
A comprehensive guide to the uses of computers in exploration where "exploration" means the application of scientific methods to discover unknown features of the earth's surface and crust. This includes the search for new mineral and oil resources as well as such related problems as identifying geologic hazards and mapping patterns of pollution. The emphasis is on the practical aspects of using computers. The principles of the various exploration techniques are given only in outline to concentrate on the problems of getting information into a computer-acceptable form, running programs in an efficient manner and maintaining flexibility in choosing analytical methods. The software to do all the tasks related to exploration data analysis is readily available, so mathematical details have not been included